FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK SOPIR BUS AKAP DI TERMINAL TERBOYO KOTA SEMARANG - Haifa Nurdiennah; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Bus drivers profession is a profession that spend many times in the city traffic. Besides, this profession is susceptible to the health problems caused by unhealthy behaviors, such as smoking habit. The study result of Institutions of Smoking Problem Prevention and Indonesian Health Consumers Empowerment Foundation towards 1.586 of bus’ drivers and conductors in five city in Indonesia showed that 82.2% of them were smoking. The purpose of the study was to analyze the factors relate to AKAP bus drivers’ smoking behaviour in Terboyo bus station Semarang city. The type of the study was quantitative study with cross sectional approach where the population were AKAP bus drivers’ that smoked in Terboyo bus station. The sample were 81 people, the sampling technique was proportional random sampling technique. The data analysis was using univariate and bivariate analysis with Chie-Square statictical test (significance level 0.05). Based on the result of the study, it was obtained, the drivers that were chategorized into heavy smoker were 79%. The Chie-Square result test showed that factor related to AKAP bus drivers’ smoking behaviour in Terboyo was regarding the knowledge (p- value 0.041), cigarettes availability (p-value 0.001), cigarettes affordability (p-value 0.002), No Smoking Area policy (p-value 0.002) and friends support (p-value 0.008). The study results showed that smoking behavior can be influenced by various factors either it was  internal or external factors. In this study, the influence of external factors dominated towards inter-provincial inter-city bus drivers’ smoking behaviour, they were, cigarettes availability, cigarettes affordability, No Smoking Area policy, and friends support. Meanwhile, age, education level, salary, attitude and family supports did not have any relationship towards AKAP bus drivers’ smoking behaviour.